Gambaran Tingkat Pengetahuan Penyakit Ginjal Dan Terapi Diet Ginjal Dan Kualitas Hidup Pasien Hemodialisis Di Rumkital Dr. Ramelan Surabaya - Aniek Kurniawati; Adhiyanti Asikin (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2018)
Background: Patients condition during haemodialysis therapy program would trigger multiple problems regarding physical and psychological condition, life style disruption, and spontaneous social changes which afflict quality of life. However, a knowledge of chronic kidney disease patients would influence healthy lifestyle attitude and behaviour in haemodialysis and diet therapies.Objectives: The objective of this research was to analyze the relationship between knowledge and quality of life in chronic renal failure (CRF) patients with haemodialysis (HD) therapy.Method: This research utilized analytical observational type with cross sectional approach. There were 53 patients as random samples. The data consisted of the characteristic, knowledge and quality of life score of CRF patients with HD therapy. Furthermore, the datas were analyzed through Spearman Correlation statistical test with CI approximately 95% (α = 0,05).Results: As many as 62.3% of respondents were categorized as having a good quality. The entire of information source were obtained from medical workers. In addition. There was a positive relation between knowledges and quality of life (p=0.023). However, based on quality of domain, only psychological health had significant relation with knowledges (p=0.014). Meanwhile, significant relations cannot be shown between knowledges and physical health (p=0.125) or social relation (p=0.277) with it.Conclusion: The quality of life of CRF with HD patients can be influenced by the level of knowledges, especially quality of life related to psychological health. There is And the role of health workers as a source of information, for it needs an effort to improve science such as attending seminars, workshops and training related profession, so it is expected to provide information according to the latest developments in scienceABSTRAKLatar Belakang: Kondisi pasien yang menjalani terapi hemodialisis akan memicu berbagai masalah seperti masalah fisik, psikologis, gaya hidup, dan perubahan sosial yang akan berdampak pada kualitas hidup pasien. Namun, dengan pengetahuan tentang penyakit ginjal dan terapi diet ginjal, yang dimiliki oleh seorang pasien gagal ginjal kronik akan mempengaruhi sikap dan perilaku hidup sehat dalam melaksanakan terapi hemodialisis dan terapi diet dengan benar.Tujuan: Penelitian ini bertujuan untuk menganalisis hubungan tingkat pengetahuan dengan kualitas hidup pasien gagal ginjal kronik (GGK) yang menjalani terapi hemodialysis (HD).Metode: Penelitian ini merupakan penelitian observasional analitik dengan pendekatan cross sectional. Sampel penelitian sebanyak 53 orang, diambil secara acak. Pengumpulan data melalui wawancara meliputi karakteristik pasien, tingkat pengetahuan dan skor kualitas hidup pasien GGK dengan HD. Analisa data yang digunakan dalam penelitian ini adalah uji statistik Spearman Correlation dengan CI sebesar 95% (α = 0.05).Hasil: Tingkat pengetahuan responden 62.3% termasuk dalam kategori baik. Sumber informasi yang diperoleh responden 100% berasal dari petugas kesehatan. Terdapat hubungan antara tingkat pengetahuan dengan kualitas hidup responden (p=0.023). Berdasarkan domain kualitas hidup, kesehatan psikologis mempunyai hubungan dengan tingkat pengetahuan (p=0.014), sedangkan kesehatan fisik (p=0.125) dan hubungan sosial (p=0.277) tidak ada hubungan dengan tingkat pengetahuan.Kesimpulan: Kualitas hidup pasien GGK dengan HD dapat dipengaruhi dari tingkat pengetahuan, terutama kualitas hidup terkait kesehatan psikologis. Peran tenaga kesehatan sebagai sumber informasi, untuk itu perlu adanya usaha untuk meningkatkan ilmu pengetahuan seperti mengikuti seminar, workshop dan pelatihan terkait profesinya, sehingga diharapkan dapat memberikan informasi sesuai perkembangan ilmu yang terbaru.